(untitled) ("Journal "U". Economy. Management. Finance.", 2018)
The article regarded the main issues and development prospects of the most problematic part of the transport infrastructure both Rostov-on-Don and Russia Federation auto transport. Its main components are investigated and the possibilities of modernization are revealed. In addition was analyzed the contribution of the FIFA World cup 2018 to the development of auto transport infrastructure. For contrast in issue of transport imbalance it was decided to compare Rostov-on-Don and Volgograd. Also, it included information about some state programs of modernization of avto transport infrastructure. Particular attention is paid to the analysis of the survey data about the condition of the auto transport infrastructure.